Jerry F. Hough y Robin Grier, The Long Process of Development: Building Markets and States in Pre-Industrial England, Spain, and Their Colonies, Nueva York, Cambridge University Press, 2015. - Arteaga, Fernando (América Latina en la Historia Económica, 2017)
No contiene Resumen